Women Writing, Written Women: The Women Figure of the Press History in Sumatra - Suriani Suriani; Syaiful Anwar (JUSPI (Jurnal Sejarah Peradaban Islam), 2022)
This paper discusses the women figures of West Sumatra and North Sumatra who came from Minang. In some respects, women figure from Minang are more advanced because both the cultural (matrilineal) system supports the level of education, which during the colonial period was better than in other areas. Three central women characters became the subject of discussions in different places, such as Rohana Kudus, Rasuna Said, and Ani Idrus. The research method is a historical method that has heuristic stages, source criticism, interpretation, and historiography. The discussion results show that the struggles of women leaders are related to the world of writing, or in other words, they are engaged in the academic field, which is not only in the world of education but also in the press.